Commodity Taxation and international Trade in Imperfect Markets - Andreas Haufler; Guttorm Schjelderup; Frank Stähler (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
This paper studies non-cooperative commodity taxation in a trade model with im-perfect competition and trade costs. Nationally optimal tax policy simultaneously tries to correct the domestic distortion from imperfect competition and to shift rents to the home country. Importantly, this trade-off depends qualitatively on the inter-national commodity tax regime in operation. For low levels of trade costs, we show that production-based commodity taxes dominate from a global welfare perspective, but this ranking is reversed in favor of consumption-based taxation when trade costs become sufficiently high.
urn:nbn:de:bsz:352-opus-5820
Keywords: 330; Verbrauchsteuer; Steuerwettbewerb; Neue Außenhandelstheorie; Strategische Handelspolitik; Ursprungslandprinzip; Steuerwirkung; Theorie